Representation Of Imbalance And Restoration In The Lion King: An Analysis Of Tzvetan Todorov's Narrative Structure And Roland Barthes' Semiotics - Anisa Puspadewi; Gina Raisah; Debby Farhani Alwy; Witri Sawalia; Mayang Pipit (International journal of technology and education research, 2026)
The Lion King has been widely analyzed through narrative, moral, and semiotic perspectives; however, most previous studies examine either the film's plot structure or its symbolic elements separately. Limited attention has been given to the relationship between narrative progression and symbolic representation in constructing ideological meanings. Therefore, this study aims to investigate how Disney's The Lion King (1994) portrays leadership, responsibility, and social order through the integration of narrative and semiotic dimensions. Employing a qualitative descriptive design, this study uses Tzvetan Todorov's narrative theory and Roland Barthes' semiotic framework as complementary analytical tools. The data consist of selected scenes, dialogues, visual symbols, and narrative events obtained from the film. Data were collected through repeated viewing, documentation, and scene classification based on Todorov's five narrative stages, followed by semiotic interpretation at the denotative, connotative, and mythological levels. The findings reveal that the transition from disequilibrium to restoration is not merely a narrative process but also a symbolic journey that redefines legitimate leadership. Key symbols, including Pride Rock, the Circle of Life, and the environmental transformation of the Pride Lands, function as visual representations of authority, accountability, and communal harmony. The study further demonstrates that leadership in the film is constructed as an ethical responsibility achieved through self-recognition and social restoration rather than inherited privilege alone. By integrating narrative and semiotic analyses, this research offers a more comprehensive understanding of how animated films communicate ideological values and contributes a novel perspective to existing studies on The Lion King.